Motivasi Wanita menjadi Memimpin (Studi di Wilayah Gerbangkertosusila-Jawa Timur) - Sumarto -; Eka Afnan Troena; Armanu Thoyib; Ubud Salim (Jurnal Aplikasi Manajemen, 2012)
There is a positive relationship between the high woman representation in public and the success of corruption and poverty eradication. This means that the role of women becomes very strategic along with the increase of woman representation in public region. In Indonesia, the problem is that woman representation is very low in public region, and from time to time it tends to decline. The low woman representation indicates that the motivation of women to lead is lower than that of men. It is estimated that work-family conflicts and the ambition of women are the significant factors which cause the low motivation of women to lead in Indonesia. The population consists of the civil servants of local governments in ”Gerbangkertosusilo” in East java. The data were collected by distributing questionnaires to respondents. Using complexity model and multiple measurement method applied to each concept in the research models, all the data were analyzed by Structural Equation Modeling (SEM), Analysis of Variance (ANOVA), and Correlation Analysis. Four relationship hypotheses were significantly proven. These significant hypotheses suggest that: 1) the motivation of women to lead is lower than that of men; 2) the higher the work-family conflict, the weaker the motivation of women to lead (in comparison with men); 3) the stronger the motivation of women to lead, the stronger the work-family conflicts; 4) the stronger the interaction between ambition and work-family conflict, the weaker the motivation of women to lead in comparison with that of men.Keywords: Work-family conflicts, Motivation to lead, Ambition